The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0969733017718395
|View full text |Cite
|
Sign up to set email alerts
|

The home as ethos of caring: A concept determination

Abstract: Based on the findings in this study, we conclude that home as ethos is an inner ethical dimension within the human being. Human beings who are in contact with their ethos, the self, feel at home and dare to follow the voice of their heart. Nurses who experience at-homeness have an ability to invite the patient into a caring relationship. The home and the feeling of being at home have significant meaning in terms of human beings' health and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 22 publications
(67 reference statements)
3
66
0
1
Order By: Relevance
“…Vaartio‐Rajalin et al, ), be prepared to discuss the situation among themselves and with the healthcare team and allow them to visit their home (cf. Hilli & Eriksson, ). Healthcare professionals, in turn, were presupposed to respect and support the patient and his/her family caregivers in all activities with the goal of achieving individual, continuous and comprehensive care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaartio‐Rajalin et al, ), be prepared to discuss the situation among themselves and with the healthcare team and allow them to visit their home (cf. Hilli & Eriksson, ). Healthcare professionals, in turn, were presupposed to respect and support the patient and his/her family caregivers in all activities with the goal of achieving individual, continuous and comprehensive care.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that patients’ preferences for outpatient treatment are not based on economic factors but instead the probability of return to hospital (Lathia et al, ). The autonomy that advanced care at home provides is based on patients’ homes being regarded as healing and loving milieus (Hilli & Eriksson, ; Lou et al, ) and not inundated with medical technical apparatuses or virtual control devices (Lindberg, Fagerström, Willman, & Sivberg, ). Another central factor in advanced care at home is patients’ family caregivers.…”
Section: Background Revised Order and Some Contentmentioning
confidence: 99%
“…When professionals overlook older persons’ opinions or fail to meet their needs and desires, the manager has the responsibility to address these concerns and provide guidance and support to the staff. Research has shown that such support can take the form of regular reflection 4042. This may be the way to strengthen the ethical competence of professionals and to engage the older person in a caring relationship so that he or she experiences a feeling of “at-homeness.” The feeling of “being home” has significance in terms of the older person’s health and well-being 40.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that such support can take the form of regular reflection 4042. This may be the way to strengthen the ethical competence of professionals and to engage the older person in a caring relationship so that he or she experiences a feeling of “at-homeness.” The feeling of “being home” has significance in terms of the older person’s health and well-being 40. Regular reflection can also reduce or prevent moral stress 43.…”
Section: Discussionmentioning
confidence: 99%
“…A distinction between being at home physically and being at home emotionally or existentially is common in the literature on dementia [68, 12] and in health and care sciences in general [1317]. In this literature, there is also an understanding of being at home as a progressive process [15, 16].…”
Section: Introductionmentioning
confidence: 99%